1997
DOI: 10.1063/1.119285
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the microstructure on the magnetic interactions in CoFe–AgCu granular films: From demagnetizing to magnetizing interactions

Abstract: The sign and strength of the dominant magnetic interactions in Co34Fe8Ag54Cu4 granular films were modified by changing the microstructure through annealing. Magnetic force micrographs showed that in the as-cast sample the magnetic moments of neighboring grains tended to be arranged parallel along a direction out of the film plane, forming elongated magnetic clusters that were themselves aligned antiparallel, with dominant demagnetizing interactions. This is a direct evidence that an uncompensated antiferromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 8 publications
2
27
1
Order By: Relevance
“…A variety of ferromagnetic/nonmagnetic granular alloys based on Co display this complex magnetic and transport behavior, the crossover FM contents within those different regimes being the only difference among them, since those values depend on the relative immiscibility of the components of each particular granular alloy. 9 A detailed study of the FeNi-Ag and CoFe-Ag͑Cu͒ granular alloys also showed similar features. …”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…A variety of ferromagnetic/nonmagnetic granular alloys based on Co display this complex magnetic and transport behavior, the crossover FM contents within those different regimes being the only difference among them, since those values depend on the relative immiscibility of the components of each particular granular alloy. 9 A detailed study of the FeNi-Ag and CoFe-Ag͑Cu͒ granular alloys also showed similar features. …”
Section: Discussionmentioning
confidence: 59%
“…These magnetic domains, much larger than the particle sizes, are stabilized due to the interplay of: ͑i͒ dipolar interactions, which tend to flux closure of neighboring magnetic domains of opposite magnetization, ͑ii͒ indirect FM interactions through the matrix, which tend to form large FM domains, and ͑iii͒ perpendicular anisotropy, arising from crystal distortion, as observed in CoFe-Ag͑Cu͒ granular alloys. 9,10 The origin of these terms in the Hamiltonian of the present granular media can be justified as follows. Dipolar interactions are intrinsic to small particle systems.…”
Section: B Mfm Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have included Fe as a minor ferromagnetic component in the largely studied Co-Ag system in order to increase GMR as previously reported, 3 and a small amount of Cu to increase immiscibility between CoFe and the nonmagnetic matrix. We have recently shown 4 the existence of an uncompensated antiferromagneticlike microstructure at volume concentrations below the percolation threshold ͓x p ϭ0.55 ͑Ref. 5͔͒ in the granular system Co 34 Fe 8 Ag 54 Cu 4 ͑xϭ0.33͒, and we have reported on magnetic interactions arising from the microstructure effecting GMR and magnetic properties.…”
mentioning
confidence: 99%
“…%. We present in this work the experimental results for samples Co 34 4 ͑sample B͒, which are representative of both different behaviors. TEM micrographs evidence the granular nature of all samples.…”
mentioning
confidence: 99%